Pengaruh Kecepatan Aliran Udara terhadap Dew Point Effectiveness (DPE) Pada Sistem Maisotsenko Cycle Indirect Evaporative Cooling Ventury Dry - Silalahi, Rafael BP; Wijaksana, Hendra; Astawa, Ketut (Teknik Desain Mekanika, 2024)
Abstract As a country with a tropical climate, Indonesia needs an air conditioning system for daily life. The use of conventional air conditioning has an impact on the environment and high energy use, so alternative air conditioning is needed, namely the Maisotsenko Cycle-Indirect Evaporative Cooling (M-IEC) air conditioning system. The main objective of this research is to determine the effect of variations in air speed on Dew Point Effectiveness (DPE) in the Maisotsenko Cycle Indirect Evaporative Cooling Ventury Dry system. The test was carried out with an 8-pass ventury dry channel type and horizontal flow control air flow with variations in air flow speed, namely 5m/s, 7 m/s, 9m/s. From the tests carried out, it was found that the highest Dew Point Effectiveness occurred at the highest air flow speed, namely 9m/s with a DPE value of 22.8%.. Keyword: M-Cycle, DPE, Air Flow Velocity, Evaporative